2018
DOI: 10.1016/j.ijpddr.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural model, functional modulation by ivermectin and tissue localization of Haemonchus contortus P-glycoprotein-13

Abstract: Haemonchus contortus, one of the most economically important parasites of small ruminants, has become resistant to the anthelmintic ivermectin. Deciphering the role of P-glycoproteins in ivermectin resistance is desirable for understanding and overcoming this resistance. In the model nematode, Caenorhabditis elegans, P-glycoprotein-13 is expressed in the amphids, important neuronal structures for ivermectin activity. We have focused on its ortholog in the parasite, Hco-Pgp-13. A 3D model of Hco-Pgp-13, present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 65 publications
3
14
0
2
Order By: Relevance
“…In our study, exposure to ABZ and ABZSO affected transcription levels of six (out of eight tested) transporter genes in H. contortus adults. However, IVMinduced changes in P-gps expression were more pronounced; particularly the expression of pgp-9.2 in the males and pgp-10, pgp-11 in the females was increased substantially [30], a result which is in agreement with the clear relationship of P-gps with IVM metabolism and resistance in nematodes [39,40]. Nevertheless, increased transcription of several P-gps after ABZ and ABZSO exposure suggests a particular role of these transporters in the metabolism of these drugs as well.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, exposure to ABZ and ABZSO affected transcription levels of six (out of eight tested) transporter genes in H. contortus adults. However, IVMinduced changes in P-gps expression were more pronounced; particularly the expression of pgp-9.2 in the males and pgp-10, pgp-11 in the females was increased substantially [30], a result which is in agreement with the clear relationship of P-gps with IVM metabolism and resistance in nematodes [39,40]. Nevertheless, increased transcription of several P-gps after ABZ and ABZSO exposure suggests a particular role of these transporters in the metabolism of these drugs as well.…”
Section: Discussionsupporting
confidence: 77%
“…The best match between each P-gp and the transcript sequences of H.contortus is displayed in Table 1. This analysis showed that the sequence HM635772 reported by Williamson and Wolstenholme (2012) as P-gp1 and used in this work for the quantification of Hco-pgp-1 by qPCR, matches the exons 26-27 from gene HCOI00233200, corresponding to P-gp17 (David et al, 2018;Laing et al, 2013). Unfortunately, the sequence HM635770 used for the design of the Hco-pgp-11 primers includes exons 5 to 7 of the same gene.…”
Section: Rna-seq Analysissupporting
confidence: 57%
“…reported by Williamson and Wolstenholme (2012) as P-gp12 and P-gp14, respectively, both match the complete P-gp13 mRNA sequence KX844966 published in GenBank (David et al, 2018) and corresponding to gene HCOI01115500 on the H. contortus reference genome (Laing et al, 2013).…”
Section: Rna-seq Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…With the use of the in silico docking approach, we provide computational evidence that the 2 forms of vitamin D can bind efficiently a close ortholog of human ABCB1. ABCB protein structures and functions are well conserved within all living kingdoms, including nematodes and mammals (31), and the nematode ABCB1 (i.e., Cel-Pgp-1) has been previously described to share similar structural features with the mammalian ABCB1 in ligand binding (22,32). Therefore, we confidently used the Cel-Pgp-1 3-dimensional structure as a relevant model for human ABCB1 in an open-inward configuration, which is supposed to be the first conformational state recognized by a substrate (21).…”
Section: Discussionmentioning
confidence: 99%